2016
DOI: 10.4103/0971-5916.191808
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/Akt/mTOR signaling & its regulator tumour suppressor genes PTEN & LKB1 in human uterine leiomyomas

Abstract: Background & objectives:Despite their high occurrence and associated significant level of morbidity manifesting as spectrum of clinical symptoms, the pathogenesis of uterine leiomyomas (ULs) remains unclear. We investigated expression profile of tumour suppressor genes PTEN (phosphatase and tensin homolog deleted on chromosome ten) and LKB1 (liver kinase B1), and key signaling components of P13K (phosphatidylinositol 3-kinase)/Akt (protein kinase B)/mTOR (mammalian target of rapamycin) pathway in leiomyomas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…In vitro experiments have confirmed that estradiol signaling can integrate a variety of extracellular signals and regulate various cellular functions, including cell growth, differentiation, transformation, and survival. Estradiol binds to the estrogen receptor and activates protein kinase pathways such as mitogen-activated protein kinase (MAPK) through the Ras-Raf-MEK-MAPK pathway and phosphatidylinositide 3-kinases (PI3K)–Akt through the PI3K–phosphatidylinositol-3,4,5-trisphosphate (PIP3)–Akt–mTOR pathway [ 25 27 ]. In the PI3K-PIP3-Akt-mTOR pathway, the binding of estradiol to receptors leads to the activation of PI3K, which in turn phosphorylates the plasma membrane lipid phosphatidylinositol-4,5-diphosphate to PIP3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro experiments have confirmed that estradiol signaling can integrate a variety of extracellular signals and regulate various cellular functions, including cell growth, differentiation, transformation, and survival. Estradiol binds to the estrogen receptor and activates protein kinase pathways such as mitogen-activated protein kinase (MAPK) through the Ras-Raf-MEK-MAPK pathway and phosphatidylinositide 3-kinases (PI3K)–Akt through the PI3K–phosphatidylinositol-3,4,5-trisphosphate (PIP3)–Akt–mTOR pathway [ 25 27 ]. In the PI3K-PIP3-Akt-mTOR pathway, the binding of estradiol to receptors leads to the activation of PI3K, which in turn phosphorylates the plasma membrane lipid phosphatidylinositol-4,5-diphosphate to PIP3.…”
Section: Discussionmentioning
confidence: 99%
“…In the PI3K-PIP3-Akt-mTOR pathway, the binding of estradiol to receptors leads to the activation of PI3K, which in turn phosphorylates the plasma membrane lipid phosphatidylinositol-4,5-diphosphate to PIP3. This process leads to the recruitment and activation of Akt proteins, which regulate mTOR, glycogen synthase kinase 3, and other proteins [ 27 ]. This pathway regulates important processes, including the cell cycle, proliferation, and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PTEN exerts tumor suppressive functions ( Keniry & Parsons, 2008 ) . It has been reported that PTEN mRNA expression was significantly increased in uterine leiomyoma tissue comparing to adjacent normal myometrium ( Makker et al ., 2016 ) . Increased PTEN activity in uterine leiomyomas might prevent the hyperactivation of the Akt pathway and produce benign tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…A known important negative regulator of Akt, tumor suppressor PTEN (phosphatase and tensin homolog), a non-redundant, evolutionarily conserved phosphatase, affects cell cycle progression, proliferation, chemotaxis and apoptosis (Keniry & Parsons, 2008). Expression of PTEN mRNA and protein levels was increased in uterine leiomyomas when com-pared to normal myometrium (Makker et al, 2016). Recent reports indicated that transcription factor PPARγ (peroxisome proliferator-activated receptor γ) transcriptionally up-regulates PTEN expression in tumor cells, with higher levels of expression of PPARγ mRNA seen in uterine leiomyomas when compared to adjacent normal myometrial tissue (Jeong et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have described up-regulated expression of other T cell checkpoints at the time of acquired resistance, including T cell immunoglobulin mucin 3 (TIM-3), lymphocyte activation gene 3 (LAG3), and V-domain immunoglobulin suppressor of T cell activation (VISTA). By comparing the pathology before treatment with PD-1 inhibitor and the biopsy after drug resistance of uterine leiomyoma, it was found that drug-resistant tumor cells had unique double allelic PTEN gene deletion, and PD-1-positive T cell infiltration was reduced, [ 98 ] suggesting that MAPK and PTEN gene mutation may be one of the mechanisms of acquired resistance by ICIs. TIM-3 is highly expressed in the tumor microenvironment, which can promote the apoptosis of Teffs, mediate the proliferation of Tregs and inhibitory cells from bone marrow, and inhibit the functions of NK cells and DC cells, thus promoting the tumor immune escape.…”
Section: Mechanisms Of Resistance To Icismentioning
confidence: 99%